Crystal Structure Analysis, Cationic and Magnetic Studies of Cobalt Ferrite Nanoparticles - Gawali, Sudarshan; Patil, Pratik S.; Ubale, Yogesh P.; Surashe, Vishnu; Jadhav, K.M. (Asian Journal of Chemistry, 2025)
In present study, we focus on the synthesis of cobalt ferrite (CoFe2O4) magnetic nanoparticles via wet chemical sol-gel self-ignition method using black pepper (Piper nigrum) as a fuel. The X-ray diffraction (XRD) investigations verified the mono-phase evolution of the simple cubic FCC type spinel structure. The crystal structure parameters, such as lattice constant (a = 8.386 Å), lattice strain, microstrain, stacking fault, etc. are obtained from XRD data and making use of the Williamson-Hall (W-H) plot. The Debye-Scherrer’s formula estimated crystallite size to be approximately 22.53 nm. The results of cation distribution suggest that cobalt ferrite have spinel structure with inverse nature. FTIR spectrum shows the two prominent absorption bands within 400 to 600 cm–1 range. The morphological study shows the spherical nature of the particle with a grain size of 14 ± 2.01 nm. Raman spectra reveal the Raman modes, viz. (A1g + Eg + 3T2g). Enhancement in saturation magnetization and decrement in coercivity were observed through the M-H curve.